BEKASI REGENCY WORKFORCE READINESS TO WORK IN THE PAPERLESS OFFICE - Fiya Fauha Umaima; Erny Hutabarat (FIRM Journal of Management Studies, 2021)
AbstractThe increasing amount of paper consumption has an impact on the environment; forest (ecosystem and species), and pollution. On the other hand, the society shifts in the direction of green environment through the growth of Paperless Office world. The purpose of this research was to investigate how capable and available the workforce is to work in the Paperless Office with substitutes such as the digital mode in carrying out their duties. Quantitative methods were used with a population of Bekasi Regency people aged 17-64 years and the sample were 155 respondents. The data were analyzed using the SPSS v.22 tool and SEM-PLS method with SmartPLS 3.0 tool. The study found that environmental awareness did not have a significant influence on workforce readiness, where the higher the level did not influence Bekasi Regency workforce readiness to work at the Paperless Office. Meanwhile, digital competence and digital usage behaviour have been found to have a significant influence on the readiness of Bekasi Regency workforce to work at the Paperless Office.